Gene expression patterns of helicoverpa armigera gut proteases - Chougule, Nanasaheb P.; Giri, Ashok P.; Sainani, Mohini N.; Gupta, Vidya S. (Insect Biochemistry and Molecular Biology, 2005)
Relative quantification of reported gut proteinase cDNAs from Helicoverpa armigera larvae fed on various host plants (cotton, chickpea, pigeonpea, tomato and okra), non-host plant Pis (winged bean, bitter gourd, ground nut, and capsicum) and during larval development has been carried out using semi-quantitative RT-PCR. Five trypsin-like and three chymotrypsin-like proteinases were categorized as insensitive or sensitive to most of the proteinase inhibitors (Pis) and insensitive/sensitive to specific Pis based on their expression analysis. These results were supported by amino acid sequence analysis, where diverged amino acids were observed in the regions, which are reported to be involved in typical trypsin trypsin inhibitor interactions and critical for proteinase inhibitor resistance. Among exopeptidases (five aminopeptidase and three carboxypeptidase), HaAmi4 and HaAmi5 of aminopeptidase and HaCar1 of carboxypeptidase exhibited considerable differential expression. Elastase and cathepsin B-like proteinases were expressed at negligible levels. The proteases identified in the study would be ideal candidates for further interactions studies with protease inhibitors to understand the structural reasons of protease inhibitor insensitivity (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: expression; gut proteinases; Helicoverpa armigera; Proteinase inhibitors; RT-PCR

Higher accumulation of proteinase inhibitors in flowers than leaves and fruits as a possible basis for differential feeding preference of Helicoverpa armigera on tomato (Lycopersicon esculentum Mill, Cv. Dhanashree) - Damle, M. S.; Giri, Ashok P.; Sainani, Mohini N.; Gupta, Vidya S. (Phytochemistry, 2005)
Tomato (Lycopersicon esculentum, Mill; cultivar- Dhanashree) proteinase inhibitors (Pis) were tested for their trypsin inhibitory (TT) and Helicoverpa armigera gut proteinases inhibitory (HGPI) activity in different organs of the tomato plants. Analysis of TI and HGPI distribution in various parts of the plant showed that flowers accumulated about 300 and 1000 times higher levels of TI while 700 and 400 times higher levels of HGPI as compared to those in leaves and fruits, respectively. Field observation that H. armigera larvae infest leaves and fruits but not the flowers could be at least partially attributed to the protective role-played by the higher levels of Pis in the flower tissue. Tomato Pis inhibited about 50-80% HGP activity of H. armigera larvae feeding on various host plants including tomato, of larvae exposed to non-host plant Pis and of various larval instars. Tomato Pis were found to be highly stable to insect proteinases wherein incubation of inhibitor with HGP even for 3 h at optimum conditions did not affect inhibitory activity. Bioassay using H. armigera larvae fed on artificial diet containing tomato PIs revealed adverse effect on larval growth, pupae development, adult formation and fecundity. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: accumulation of PI; Helicoverpa armigera; Lycopersicon esculentum; Midgut proteinases; Plant defense; Proteinase inhibitors

In vivo and in vitro effect of capsicum annum proteinase inhibitors on helicoverpa armigera gut proteinases - Tamhane, V. A.; Chougule, Nanasaheb P.; Giri, Ashok P.; Dixit, A. R.; Sainani, Mohini N.; Gupta, Vidya S. (Biochimica Et Biophysica Acta-General Subjects, 2005)
Two proteinase inhibitors (PIs), CapA1 and CapA2, were purified from Capsicum annum Linn. Var. Phule Jyoti leaves and assessed for their in vitro and in vivo activity against Helicoverpa armigera gut proteinases (HGPs). Both the inhibitors exhibited molecular weights of about 12 kDa with inhibitory activity against bovine trypsin and chymotrypsin indicating presence of probable two-inhibitor repeats of PIN II family. CapA1 and CapA2 inhibited 60-80% HGP (azocaseinolytic) activity of fourth instar larvae feeding on various host plants while 45-65% inhibition of HGP activity of various instars (II to VI) larvae reared on artificial diet. The partial purification of HGP isoforms, their characterization with synthetic inhibitors and inhibition by C. annum PIs revealed that most of the trypsin-like activity (68-91%) of HGPs was sensitive to C. annum PIs while 39-85% chymotrypsin-like activity of HGPs was insensitive to these inhibitors. The feeding of C. annum leaf extracts and two purified PIs in various doses to H. armigera larvae for two successive generations through artificial diet demonstrated their potential in inhibiting larval growth and development, delay in pupation period and dramatic reduction in fecundity and fertility. This is the first report-demonstrating efficacy of C. annum PIs against insect gut proteinases as well as larval growth and development of H. armigera. (c) 2004 Elsevier B.V. All rights reserved.
Keywords: Capsicum annum; gut proteinase; Helicoverpa armigera; insect resistance; Proteinase inhibitor